The relationship between fear of crime and risk perception across Europe - Krulichová, Eva (Criminology & criminal justice, 2019)
Cross-national comparisons of fear of crime have been gaining in popularity within the academic community, as they allow for the examination of both individual and country-level correlates of this phenomenon. Nevertheless, the role of perceived victimization risk in fostering fear of crime with respect to various country specifics is often neglected. Drawing on data from the European Social Survey Round 5 (ESS R5), the aim of this study is to explore the relationship between fear of crime and risk perception in the context of 23 European countries. Risk perception is positively correlated with fear of crime in all of the analysed countries, although the strength of the relationship differs. Contrary to expectations, countries with a higher victimization rate exhibit a weaker relationship between fear of crime and risk perception, while in countries with a lower victimization rate, risk perception plays a relatively important role in shaping fear of crime. No effect of unemployment rate, size of migrant population or income inequality was found in the data.